Counseling theories and techniques for rehabilitation and mental health professionals - Chan, Fong;Berven, Normal L.;Thomas, Kenneth R. (New York, NY : Springer Publishing Company, 2015)
The only text about counseling theories and techniques developed specifically for upper-level rehabilitation counseling students and practitioners, this book is now fully updated with a focus on evidence-based practice. It reflects the great strides made in incorporating research-based knowledge into counseling/therapy interventions since the first edition's publication nearly 10 years ago. The book disseminates the expertise of many of the most esteemed leaders and academic scholars in rehabilitation counseling. These authors emphasize state-of-the-art scientific evidence.
Part 1. Introduction -- 1. An introduction to counseling for rehabilitation and mental health professionals -- Part 2. Counseling theories -- Humanistic approaches -- 2. Person-centered counseling -- 3. Solution-focused brief therapy -- 4. Gestalt therapy -- Cognitive and behavioral approaches -- 5. Cognitive behavioral therapy -- 6. Rational emotive behavior therapy -- 7. Behavior therapy -- 8. Trait-factor theory and counseling process -- Psychodynamic approaches -- 9. Psychodynamic therapy -- 10.Adlerian therapy -- Part 3. Basic techniques -- 11. Basic counseling skills -- 12. Motivational interviewing -- 13. Group procedures -- 14. A family systems and social-ecological perspective for rehabilitation health professionals -- 15. Career and vocational counseling -- Part 4. Special considerations -- 16. Substance use disorders, disability and counseling interventions -- 17. Counseling people with physical disabilities -- 18. Counseling interventions for people with psychiatric disabilities -- 19. Multicultural rehabilitation counseling: optimizing success with diversity -- Part 5. Professional issues -- 20. Clinical supervision -- 21. Managing risk in professional practice.
Includes bibliographical references and index.
Keywords: PEOPLE WITH DISABILITIES